ANALISIS STRATEGI PEMASARAN UMKM PADA MASA PANDEMI COVID – 19 DI KOTA DENPASAR - Putu Ari Mulyani; Ni Luh Indiani (Forum Manajemen STIMI Handayani Denpasar, 2021)
Micro, Small and Medium Enterprises (MSMEs) are currently experiencing difficulties due to the Covid-19 pandemic which has made the economy decline. MSMEs as one of the supporting forces for Indonesia's economic growth, especially in Denpasar City, Bali Province, should get more attention from the local government. In the midst of pandemic like this, internal environmental factors and external factors are an obstacle for MSME actors. In anticipating these environmental changes and not having a marketing strategy, MSMEs have no competitiveness compared to other products. This study uses SWOT analysis which is the right alternative to helphave MSMEs determine marketing strategies and anticipate environmental changes due to the Covid-19 pandemic both from internal factors: strength (strength), weakness (weaknesess) while threats (Threats), opportunities (Opportunities) is part of external factors or competitors. From this research, it was found that there were 4 marketing strategies for MSMEs to increase competitiveness, namely the S-O Strategy for MSMEs to innovate products, make characteristics of the products being sold and utilize technology to market products. The W-O strategy, MSME players must look at the consumer market share, and the W-T Strategy introduces products in areas outside the city of Denpasar and innovative product packaging. Government policies are very important in terms of the assisting MSMEs through grant funding programs and banking policies in the form of low interest capital loans.